2011
DOI: 10.1371/journal.pone.0015893
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membrane Factor XIIIA Transglutaminase Activity Regulates Osteoblast Matrix Secretion and Deposition by Affecting Microtubule Dynamics

Abstract: Transglutaminase activity, arising potentially from transglutaminase 2 (TG2) and Factor XIIIA (FXIIIA), has been linked to osteoblast differentiation where it is required for type I collagen and fibronectin matrix deposition. In this study we have used an irreversible TG-inhibitor to ‘block –and-track’ enzyme(s) targeted during osteoblast differentiation. We show that the irreversible TG-inhibitor is highly potent in inhibiting osteoblast differentiation and mineralization and reduces secretion of both fibrone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 101 publications
(131 reference statements)
4
42
0
Order By: Relevance
“…Several soluble factors, including adipokines and cytokines, exert a regulatory effect on the activity of different bone marrow cell populations, suppressing or promoting haematopoiesis, osteogenesis, and bone resorption [35,36] The rearrangement of MTs, the major component of the cytoskeleton, is involved in the regulation of differentiation processes and predispose cells to acquire a functional mature phenotype [37][38][39]. The analysis of MTs organization by immunofluorescence microscopy showed a strong rearrangement of tubulin in hMSC maintained for 7 days at low extracellular [Na ?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several soluble factors, including adipokines and cytokines, exert a regulatory effect on the activity of different bone marrow cell populations, suppressing or promoting haematopoiesis, osteogenesis, and bone resorption [35,36] The rearrangement of MTs, the major component of the cytoskeleton, is involved in the regulation of differentiation processes and predispose cells to acquire a functional mature phenotype [37][38][39]. The analysis of MTs organization by immunofluorescence microscopy showed a strong rearrangement of tubulin in hMSC maintained for 7 days at low extracellular [Na ?…”
Section: Discussionmentioning
confidence: 99%
“…of 115 mM and became more evident at 90 mM, with partial disruption of MTs. This event, even allowing osteoblast differentiation [37], can affect cell function, in particular the secretion of matrix molecules [38]. As a consequence bone quality might be impaired, contributing to the bone fragility observed in hyponatremic patients [6].…”
Section: Discussionmentioning
confidence: 99%
“…However, Al-Jallad et al (16) reported that FXIIIA could play a major role in MC3T3-E1 cell differentiation and collagen I matrix formation, and TG2 crosslinking activity did not contribute to osteoblast differentiation (16,24). However, in the current study, although we did not assay the expression of FXIIIA, we did find that TG2 levels continued to increase steadily during osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of endogenous TG activity in preosteoblast cultures with cystamine resulted in complete abrogation of mineralization, attributable to reduced ECM accumulation and an arrested state of osteoblast differentiation (Al-Jallad et al, 2006); however, recent evidence indicated that FXIIIA rather than TG2 acted as the major regulator of ECM deposition (Al-Jallad et al, 2011). Finally, TG2-induced osteoblast-like transformation of phenotypically plastic cells, such as vascular smooth muscle cells (Faverman et al, 2008), suggested that TG2 may be critical for vascular calcification (Johnson et al, 2008a).…”
Section: Roles Of Tg2 In Cellular Processesmentioning
confidence: 99%